2017
DOI: 10.1097/aog.0000000000001936
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Adverse Pregnancy Outcome After Paternal Exposure to Methotrexate Within 90 Days Before Pregnancy

Abstract: We found no association between paternal exposure to methotrexate within 90 days before pregnancy and congenital malformations, stillbirths, or preterm birth. Available data suggest that prepregnancy paternal methotrexate exposure should not be of major concern. Multinational recommendations should be changed accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Although the drug label suggests discontinuation of MTX before attempting pregnancy, data show no evidence for mutagenesis or teratogenicity .…”
Section: Results/recommendationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the drug label suggests discontinuation of MTX before attempting pregnancy, data show no evidence for mutagenesis or teratogenicity .…”
Section: Results/recommendationsmentioning
confidence: 96%
“…In men with RMD who are planning to father a pregnancy, we conditionally recommend, based on a smaller body of evidence, continuing treatment with MTX, MMF, leflunomide, sulfasalazine, calcineurin inhibitors, and nonsteroidal antiinflammatory drugs (NSAIDs) ( ).…”
Section: Results/recommendationsmentioning
confidence: 99%
“…It is recommended that men stop methotrexate three months before conception. Two recent observational studies did not find an increased risk of congenital malformations when methotrexate (<30 mg) was used 90 days before conception 20,21. Condoms are not required during pregnancy.…”
Section: Methotrexatementioning
confidence: 97%
“…Data regarding preconception exposure to MTX in men are reassuring, and, indeed, recent BSR guidelines state there is no need for men wishing to father children to stop MTX [154]. A study involving a very large cohort concluded that paternal exposure to MTX within 90 days before pregnancy was not associated with congenital malformations, stillbirths, and preterm birth [155]. Older recommendations suggest to stop MTX three months prior to conception, but this is not evidenced by an understanding of the impact of MTX on spermatogenesis or paternal-mediated teratogenicity, but rather relies on the timeframe of spermatogenesis [156].…”
Section: How To Get the Most Out Of Mtx As A First-line Treatment?mentioning
confidence: 99%